Україна та українські льотчики в російській військовій авіації (в період до 1917 р.) - Пістоленко, І.О. (Питання історії науки і техніки, 2008)
Статья посвящена истории создания и деятельности первых авиационных военных формирований, учебных заведений, состоянию авиационной промышленности на
территории Украины в первые десятилетия ХХ века (до 1917 года). Рассматриваются основные события и степень представительства и участия украинских летчиков в
становлении и развитии военной авиации Российской империи. The article is dedicated to the history of the foundation and work of the first aircraft military
units, educational institutions, to the state of the aircraft industry in the territory of
Ukraine in the first decades of the twentieth century (till 1917). The main events and the degree
of representation and the participation of Ukrainian pilots in the formation and development
of military aviation of Russian Empire are also revealed.